New evidence of early Iron Age to Medieval settlements from the southern fringe of Thar Desert (western Great Rann of Kachchh), India: Implications to climate-culture co-evolution. (March 2020) - Sarkar, Anindya; Mukherjee, Arati Deshpande; Sharma, Shubhra; Sengupta, Torsa; Ram, F.; Bera, M.K.; Bera, Subir; Biswas, Oindrila; Thakkar, M.G.; Chauhan, G.; Yadava, M.G.; Shukla, A.D.; et al.
Abstract: Two hitherto unexplored settlements at Karim Shahi and Vigakot are reported from the uninhabited hyper-arid region of the western Great Rann of Kachchh (GRK), located near southern fringe of Thar Desert, Gujarat, NW India. The archaeological evidence, supported by radiocarbon and optical chronology indicate presence of settlement from the Early Iron Age to Early Historic ( 3100–2300 years B.P.) and Historic to Medieval ( 1500–900 years B.P.) periods. This would imply that following the Harappan decline, the GRK was still a hospitable terrain for the sustenance of human settlements' during the Early Iron Age. Isotopic and micro-botanical evidence indicate that relatively higher rainfall than today sustained the hydrological system until around the Medieval period. We propose that the early withdrawal of the late Holocene Inter Tropical Convergence Zone (ITCZ) and resultant monsoon decline accounts for the abandonment of settlement in the western (Sindh-Baluchistan) domain. As a consequence, the rivers in the western domain dried early, while the fluvial system in the southern/eastern domain (Sorath/Cholistan in Gujarat/Ghaggar-Hakra-Nara interfluve) was sustained due to monsoonal rain at least up to 1600 years B.P. The settlements were subsequently disrupted due to a combination of hyper-arid climate and infrequent tectonic activity sometime between the late Medieval and recent time. The settlement migration in the southern/eastern domain, as far into the Rann and desert fringe during this period was possibly a nonpareil ancient analogue of modern "climate refugee and refugia" (Warner, 2011 ; Morelli et al., 2016 ) induced by anthropogenic climate change. Highlights: Two unknown ancient settlements, Karim Shahi and Vigakot, are documented from Thar Desert and Great Rann of Kachchh, India. After the Harappan decline, human settlement continued from Early Iron Age to Medieval ( 3100-900 year B.P.) period. Palaeoclimate data suggest relative higher rainfall, C3 vegetation during this period. Early withdrawal of the ITCZ and monsoon failure is implicated for cultural collapse and human migration from west to east.